2013
DOI: 10.5606/ehc.2013.20
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of gonadal shielding in pediatric pelvis X-rays

Abstract: Amaç: Bu çalışmada gonad koruyucuların pediatrik hastalarda kullanımının etkinliği değerlendirildi. Hastalar ve yöntemler: Ekim 2011 -Şubat 2012 tarihleri arasında hastanemizde çekilen ardışık 675 hastanın (323 erkek, 352 kız; ort. yaş 6.8 yıl; dağılım 6 ay-17 yıl) 1137 pelvis röntgeni, gonad koruyucu kullanımı açısından, bir ortopedist, bir jenekolog ve bir pediatristten oluşan bir ekip tarafından değerlendirildi. Bulgular: İncelenen 1137 röntgenden 566'sında (%49.8) gonad koruyucu kullanıldığı ve bunlardan 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Reported negative effects ("risks") of shielding include [7] the following: testes dose reduction of less than 95% due to misplaced shields (e.g. 77% in 10-15-year olds) [7], the need of retakes (Gürsu et al reported a retake rate of 3% in children up to 17 years) [90], a dose increase if the shield covers (part of) the automatic exposure control (AEC) detector [13], and loss of diagnostic information, and distraction of the technologist by handling the shield. The small risk reductions seen at the bottom of Table 5 (a risk < 1 × 10 −6 is considered inconsequential [91]) have to be viewed in the light of such effects.…”
Section: Discussionmentioning
confidence: 99%
“…Reported negative effects ("risks") of shielding include [7] the following: testes dose reduction of less than 95% due to misplaced shields (e.g. 77% in 10-15-year olds) [7], the need of retakes (Gürsu et al reported a retake rate of 3% in children up to 17 years) [90], a dose increase if the shield covers (part of) the automatic exposure control (AEC) detector [13], and loss of diagnostic information, and distraction of the technologist by handling the shield. The small risk reductions seen at the bottom of Table 5 (a risk < 1 × 10 −6 is considered inconsequential [91]) have to be viewed in the light of such effects.…”
Section: Discussionmentioning
confidence: 99%
“… The highly attenuating material of the shielding may interfere with automatic exposure control systems and can lead to an increase rather than a decrease in patient dose [ 3 , 17 ]. Beam hardening or streak artefacts caused by the applied shielding can reduce the image quality and may lead to the requirement to repeat the exposure [ 18 ]. …”
Section: Evidence For Changementioning
confidence: 99%
“…Beam hardening or streak artefacts caused by the applied shielding can reduce the image quality and may lead to the requirement to repeat the exposure [ 18 ].…”
Section: Evidence For Changementioning
confidence: 99%
“…Bu da, röntgende olduğu gibi daha etkili koruyucu önlemler alınmasına katkıda bulunacaktır. [24] Çıkar çakışması beyanı Yazarlar bu yazının hazırlanması ve yayınlanması aşamasında herhangi bir çıkar çakışması olmadığını beyan etmişlerdir.…”
Section: Gereç Ve Yöntemlerunclassified